2015
DOI: 10.1080/1359432x.2015.1046048
|View full text |Cite
|
Sign up to set email alerts
|

The mitigating role of leader‒member exchange when perceiving psychological contract violation: a diary survey study among volunteers

Abstract: The accuracy of the Content should not be relied upon and should be independently verified with primary sources of information. Taylor and Francis shall not be liable for any losses, actions, claims, proceedings, demands, costs, expenses, damages, and other liabilities whatsoever or howsoever caused arising directly or indirectly in connection with, in relation to or arising out of the use of the Content. This article may be used for research, teaching, and private study purposes. Any substantial or systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 81 publications
9
86
0
Order By: Relevance
“…We contacted respondents via email and asked them to complete a general demographic survey prior to completing ten short daily surveys. We chose this design because (1) several scholars have demonstrated the short-term volatile nature of our concepts under study (e.g., Dalal, Lam, Weiss, Welch, & Hulin, 2009;Griep et al, 2016;Johnson & O'Leary-Kelly, 2003), (2) recall errors are far less likely to occur with shorter time intervals (e.g., Mitchell & James, 2001), and (3) a 2week record-keeping period represents a stable and generalizable estimate of life (Wheeler & Reis, 1991). We sent daily surveys at 4 PM and gave respondents until midnight to complete the survey.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We contacted respondents via email and asked them to complete a general demographic survey prior to completing ten short daily surveys. We chose this design because (1) several scholars have demonstrated the short-term volatile nature of our concepts under study (e.g., Dalal, Lam, Weiss, Welch, & Hulin, 2009;Griep et al, 2016;Johnson & O'Leary-Kelly, 2003), (2) recall errors are far less likely to occur with shorter time intervals (e.g., Mitchell & James, 2001), and (3) a 2week record-keeping period represents a stable and generalizable estimate of life (Wheeler & Reis, 1991). We sent daily surveys at 4 PM and gave respondents until midnight to complete the survey.…”
Section: Methodsmentioning
confidence: 99%
“…Because one's colleagues cannot be held responsible for upholding the PC between an employee and his or her employer, CWB-I is an unlikely outcome in the aftermath of PCB(Griep, Vantilborgh, Baillien, & Pepermans, 2016). Hence, I only focused on CWB-O and CWB-S throughout the remainder of this paper.…”
mentioning
confidence: 99%
“…Studies have shown that psychological contract violation is negatively related to outcomes such as job satisfaction (Callea et al, 2016), turnover intentions (e.g., Arshad, 2016; Salin and Notelaers, 2017), depressive mood states (Priesemuth and Taylor, 2016) and counterproductive behavior (Griep et al, 2016). Yet, there is not a lot of knowledge and understanding about the way in which employees cope with psychological contract violation and how the coping process leads to restoration of the psychological contract.…”
Section: Introductionmentioning
confidence: 99%
“…Bal & Kooij, 2011;Hess & Jepsen, 2009;Lub, Bal, Blomme, & Schalk, 2016;Nikolaou, Tomprou, & Vakola, 2007;Orvis, Dudley, & Cortina, 2008;Raja et al, 2004); and, various moderating and mediating mechanisms of PC breach effects (e.g. Deery, Iverson, & Walsh, 2006;Griep, Vantilborgh, Baillien, & Pepermans, 2016;Montes & Irving, 2008;Robinson, 1996;Turnley, Bolino, Lester, & Bloodgood, 2004). Research has identified and remedied various methodological shortcomings (e.g.…”
Section: Psychological Contractsmentioning
confidence: 99%
“…Bankins, 2015) and the dynamics of PC processes over time (e.g. Griep, Vantilborgh, Baillien, et al, 2016;Solinger, Hofmans, Bal, & Jansen, 2016).…”
Section: Psychological Contractsmentioning
confidence: 99%